Mức sẵn lòng trả của người tiêu dùng cho tuyến Metro số 1 tại TP. Hồ Chí Minh - Lê Thanh , Loan; Lê Tuấn , Anh (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2017)
This study estimates willingness to pay (WTP) of potential customers for Metro Line 1 of Ho Chi Minh City-based Metro Project by using contingent valuation method and undertakes assessment of the transportation situation in Ho Chi Minh City. The estimated rate at which they are willing to pay for the service is VND9,320/passenger/turn, and the most common WTP ranges from VND8,000–12,000/passenger/turn. The factors that positively influence WTP include the benefits of Metro Line 1 to the individual consumer (namely flexibility and time of transportation), current transportation cost of respondents, income, and gender. The social and environmental benefits of Metro, though being highly evaluated, do not significantly affect the willingness to pay for Metro Line 1. The study provides the common range of WTP and the average estimated WTP as a basis for pricing policy so as to deploy this line. The promotion strategy for Metro Line 1 should prioritize the benefits of Metro to individual consumers.
Keywords: Willingness to pay; Metro; Tobit model; Ho Chi Minh City